Epsilon-Nets, Unitary Designs, and Random Quantum Circuits - Oszmaniec, Michal; Sawicki, Adam; Horodecki, Michal (IEEE transactions on information theory, 2022)
Epsilon-nets and approximate unitary t -designs are natural notions that capture properties of unitary operations relevant for numerous applications in quantum information and quantum computing. In this work we study quantitative connections between these two notions. Specifically, we prove that, for d dimensional Hilbert space, unitaries constituting δ -approximate t -expanders form ε -nets for t\simeq \frac {d^{5/2}}{ ε } and δ \simeq \left ({\frac { ε ^{3/2}}{d}}\right)^{d^{2}} . We also show that for arbitrary t , ε -nets can be used to construct δ -approximate unitary t -designs for δ \simeq ε t , where the notion of approximation is based on the diamond norm. Finally, we prove that the degree of an exact unitary t design necessary to obtain an ε -net must grow at least as fast as \frac {1}{ ε } (for fixed dimension) and not slower than d^{2} (for fixed ε ). This shows near optimality of our result connecting t -designs and ε -nets. We apply our findings in the context of quantum computing. First, we show that that approximate t-designs can be generated by shallow random circuits formed from a set of universal two-qudit gates in the parallel and sequential local architectures considered in (Brandão et al., 2016). Importantly, our gate sets need not to be symmetric (i.e., contains gates together with their inverses) or consist of gates with algebraic entries. Second, we consider compilation of quantum gates and prove a non-constructive Solovay-Kitaev theorem for general universal gate sets. Our main technical contribution is a new construction of efficient polynomial approximations to the Dirac delta in the space of quantum channels, which can be of independent interest.